Investigation of Mixing Gelling Agents on the Taste and Texture of Plant-Based Chicken Products. - Ali Haider Khokhar 1997- (2025)
The main purpose of this thesis was to study the effect of different gelling agents on plant-based chicken nuggets and compare them to two market-based products. The comparison was done through sensory evaluation and consumer testing of the products. Different attributes like color, texture and flavor were evaluated. The research had four key objectives: determining the optimal water-to-Texturized Pea Protein (TPP) ratio for the base recipe, assessing the effectiveness of different gelling agents, optimizing gelling agent concentrations to improve sensory qualities, and comparing the final products with market-based products. First the base recipe of water to TPP ratio was found by performing different tests. After that the gelling agents that gave the best results individually were selected for further testing. Thes selected gelling agents were Kappa Carrageenan, Super Agar, and Konjac Glucomannan. After this, different concentrations of these gelling agents along with base recipe were tested to make two final products that gave the best results based upon sensory evaluation. These two final products were then compared to two market-based products. Results showed that the product with equal concentrations of the three selected gelling agents matched the market products in attributes like moisture, color, and crispiness. Similarly, the product with twice the Kappa Carrageenan concentration received comparable scores in moisture, texture, color, meat similarity, and crispiness. Consumer evaluation was used during the experiment. In conclusion, the final two products prepared in the lab performed similarly to market-based products in most sensory attributes, demonstrating their potential as competitive plant-based chicken alternatives. Through improved further testing and by applying more sensory evaluations methods these two lab-based products can be introduced into the market. Loki Foods (Iceland)